2018
DOI: 10.29261/pakvetj/2018.053
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of the PRNP Gene Polymorphisms in Binglangjiang Buffalo (Bubalus bubalis) for Comparing Potential Susceptibility to BSE

Abstract: The bovine spongiform encephalopathy (BSE), is a neurodegenerative disorder initiated by miss folded prion protein affecting in cattle. It is associated with a 23 bp indel polymorphism in the putative promoter and a 12 bp indel in intron 1 of the PRNP gene. There is no prior record of investigating for these indels polymorphism from Binglangjiang (BLJ) buffalo. The results of collected 100 samples from BLJ buffalo demonstrated that high insertion of genotype frequencies in 23++ (0.98) and 12++ (0.93) with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…BSE is a fatal neurodegenerative disorder caused by abnormal metabolism of prion protein (PrP) [30][31][32][33][34][35]. It has been reported that these cellular prion proteins (PrP C ) are encoded by prion proteins whose expressions show a vital role in prion disease susceptibility [36].…”
Section: Discussionmentioning
confidence: 99%
“…BSE is a fatal neurodegenerative disorder caused by abnormal metabolism of prion protein (PrP) [30][31][32][33][34][35]. It has been reported that these cellular prion proteins (PrP C ) are encoded by prion proteins whose expressions show a vital role in prion disease susceptibility [36].…”
Section: Discussionmentioning
confidence: 99%
“…BSE is a fatal neurodegenerative disorder caused by abnormal metabolism of prion protein (PrP) [31][32][33][34][35] . It has been reported that these cellular prion proteins (PrP C ) are encoded by prion protein whose expression shows a vital role in prion disease susceptibility 36 .…”
Section: Discussionmentioning
confidence: 99%